Typographic enhancement of multiword units in second language text. (25th April 2016) - Boers, Frank; Demecheleer, Murielle; He, Lin; Deconinck, Julie; Stengers, Hélène; Eyckmans, June
Abstract : This study examines the effect of typographic enhancement on L2 learners' intake of multiword units from reading. EFL learners read texts in one of three versions: (1) with many multiword units underlined; (2) with half of these multiword units underlined; and (3) without any underlining. The learners were subsequently asked to identify the multiword units they remembered encountering in the texts. The purpose of the text version in which only half of the target units were underlined was to explore whether enhancement of a small number of word strings in a text also stimulates intake of others from that text. As expected, enhanced multiword units were remembered better than unenhanced ones, but there was no evidence that the benefit extended beyond the enhanced items.